EFFECT OF ORGANIC AND INORGANIC SELENIUM WITH AND WITHOUT VITAMIN E ON IMMUNE SYSTEM OF BROILERS - M.I. Hussain, S.A. Khan, Z.I. Chaudhary, A. Aslam, K. Ashraf1 and M.F. Rai (Pakistan Veterinary Journal, 2004)
The present project was designed to investigate effects of organic and inorganic selenium with and without vitamin E on the immune system of broiler chickens. For this purpose, 130 (day-old) broiler chicks were divided into three groups A, B (60 chicks each) and C (10 chicks). Group A was divided into six subgroups A1, A2, A3, A4, A5 and A6 which were fed on organic selenium at dose rates of 0.25, 0.25, 0.5, 0.5, 1.0 or 1.0 mg/kg and vitamin E at the dose rates of 0, 200, 0, 200, 0 or 200 IU/kg, respectively. Group B was also divided into six subgroups B1, B2, B3, B4, B5 and B6, which were fed on inorganic selenium at dose rates of 0.25, 0.25, 0.5, 0.5, 1.0 or 1.0 mg/kg and vitamin E at the dose rates of 0, 200, 0, 200, 0 or 200 IU/kg, respectively. Group C (control) received no selenium or vitamin E. Parameters studied were haemagglutination inhibition antibody titre against Newcastle disease virus, pathological examination of lymphoid organs, lymphoid organs weight/body weight ratio and growth traits. Results showed that the effects of organic selenium supplementation were better than that of inorganic selenium. Moreover, the effects of organic or inorganic selenium with vitamin E were better than the supplementation of organic or inorganic selenium without vitamin E.